Composition uniformity and large degree of strain relaxation in MBE-grown thick GeSn epitaxial layers, containing 16% Sn. (18th February 2021) - Rathore, Jaswant; Nanwani, Alisha; Mukherjee, Samik; Das, Sudipta; Moutanabbir, Oussama; Mahapatra, Suddhasatta
Abstract: We systematically investigate the compositional uniformity, degree of strain relaxation (DSR), defect structure and surface morphology of GeSn epitaxial layers with 16% Sn, grown by low temperature molecular beam epitaxy (MBE) on Ge-buffered Si(001) substrates. Combining atom probe tomography, reciprocal space mapping, cross-sectional transmission electron microscopy, and atomic force microscopy analyses, we demonstrate that for a layer thickness of t GeSn = 250 nm, a high DSR (∼70%) can be achieved, while maintaining compositional uniformity at the atomic scale. We find no evidence of Sn clustering in the bulk, or Sn segregation to the surface, for at least this value of t GeSn . The observed compositional uniformity contrasts the well-established phenomenon of strain-relaxation enhancement of Sn content in chemical vapour deposition (CVD) growth of GeSn. The defect structure leading to strain relaxation in these MBE-grown GeSn epitaxial layers is also distinctly different from that observed in CVD growth of the alloy. We observe the co-existence of highly strain-relaxed and pseudomorphically strained regions in the grown epilayers, tentatively explained by bunching of threading dislocations. Considering that MBE growth of GeSn epitaxial layers, with such high-Sn content and layer thickness, has not been reported before, our results are encouraging for future improvements in design and fabrication of group-IV-based mid-infrared photonic devices.